Indícios de autoria em textos dissertativo-argumentativos do Exame Nacional do Ensino Médio - ENEM - Sobrinho, Viviane Vieira de (2020)
The idea for this research arose from reflections and questions about the concept of authorship that is oriented by the National High School Examination (ENEM) participant’s booklet. It was perceived that the referred manual does not clarify, in fact, what it is an original composition, casting the participant adrift in such an important test, which is the main opportunity for the admission to Brazilian universities. In addition, it is possible to interpret that the test seems to emphasize the form, textual organization, instead of the discursive aspects, that are, in fact, relevant for the author’s mark. Based on that, this study aims to analyze how the contextual elements, specifically the originality and the responsivity, can highlight the authorship in dissertative-argumentative texts produced by the participants of ENEM. The data analysis is based on Bakhtin (2000) and Possenti (2002). This is a descriptive, qualitative study, which examines the corpus that was formed from the previous analysis of 17 compositions scored one thousand, from the ENEM that took place in 2016 and 2017. The compositions were written by the participants who applied for the undergraduate courses, which have as requirement the performance grade (which can vary from zero to one thousand), this grade is, therefore, the determining factor for the applicants’ approval that are, in majority, soon-to-be high school graduates. As a result, it is possible to state that the notion of authorship is associated with: enunciation; style; and the position taken by the author. First, the author activates other utterers as a basis to demonstrate to the reader/evaluator that his/her interpretation about the topic is aligned with other utterers. Second, the text building happens through a style; in this case, it is a set of strategies that highlights or not some of the argumentation items, in order to avoid the representation of a common view, as this process emphasizes its tone of singularity. Third, the thesis advocated by the participant reveals itself as his/her position. These findings reveal that the authorship is noticeable in the discursive formulations, as it provides the necessary procedures to implement the strategies that enable the uttering. Therefore, the discursive notion needs to be explained in the written process of the ENEM candidates.